Biomimetic Total Synthesis of (−)‐Penibruguieramine A Using Memory of Chirality and Dynamic Kinetic Resolution. Issue 37 (21st July 2015) - Kim, Jae Hyun; Lee, Seokwoo; Kim, Sanghee
Abstract The fully stereocontrolled total synthesis of (−)‐penibruguieramine A, a naturally occurring marine pyrrolizidine alkaloid, is described in this study for the first time. The key synthetic sequence is the biomimetic aldol reaction of the proline pentaketide amide. The principles of "memory of chirality" (MOC) and "dynamic kinetic resolution" (DKR) are applied to this reaction for the asymmetric synthesis using proline as the only chiral source. A mechanistic rationale is discussed for the excellent stereochemical outcome in a protic solvent environment.